Peran Hukum dalam Mencegah Eksploitasi Anak: Tinjauan Regulasi dan Penegakan Hukum Pidana di Indonesia - Geri Ardji Novandi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Child exploitation is a serious issue that threatens the fulfillment of children's fundamental rights and impacts their physical, psychological, and social development. This study aims to analyze the role of law in preventing child exploitation through an examination of regulations and criminal law enforcement in Indonesia. The method used is normative juridical research with a descriptive qualitative approach, supported by empirical data from interviews with law enforcement officers and child protection agencies. The results of the study indicate that although Indonesia has a comprehensive regulatory framework, such as Law Number 35 of 2014 concerning Child Protection and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, its implementation still faces various challenges. These obstacles include weak coordination among institutions, limited capacity of law enforcement officers, low public awareness, and the persistent social stigma against child victims. This study emphasizes the importance of strengthening the capacity of officers, applying a restorative approach, fostering synergy among institutions, and public education to build an effective, integrative, and sustainable child protection system.